Antibody-Binding Motif of Mimetic Peptides to V. cholerae O139 Lipopolysaccharide - Aree Thattiyaphong; Amornrat Promboon; Chaivat Kittigul; Krongkaew Supawat; Pathom Sawanpunyalert; Sunanta Ratanapo (Agriculture and Natural Resources, 2006)
This study explores deduced amino acid sequences of mimetic peptides of Vibrio cholerae O139 epitopes in order to design specific antigens for use in diagnostic method. Mimetic peptides expressed on E. coli flagella were selected from a FliTrx random peptide library via the interaction with purified monoclonal antibody to V. cholerae O139. Inserted nucleotides encoding bound peptides were determined by PCR. Peptides from clones giving positive results were confirmed by Western blot analysis. Sixty-two positive E. coli colonies were obtained and nucleotide-sequenced. Inserted nucleotides were translated into amino acids. Fifty-six patterns of deduced amino acid sequences were obtained without a consensus sequence. Most sequences of mimetic peptides have amino acid motif as RXXR with approximate molecular weight of 1,700 to 2,000. Arginine and glycine occupy the highest percentage of amino acid composition.